The level of effectiveness of healthcare education on TikTok - Khairul Azli, Najmi Nafis; Mohd Rizal, Siti Hana Natasya; Ridzuan, Abdul Rauf; Baharuddin, Nur Umairah Bazla; Mahlin, Muhamad Aiman; Sataria, Iskhandar Ishraf; Jamri, Mohamad Hafifi (Faculty of Communication and Media Studies, 2025)
This study explores the effectiveness and awareness levels of healthcare education on TikTok, focusing on combating unhealthy diet and obesity. Utilizing surveys and statistical analysis, it aims to assess TikTok's impact on educating users about health topics and measure the level of audience awareness. TikTok has emerged as an unexpected but potent platform for healthcare education, enabling healthcare practitioners to disseminate factual information through engaging short videos. The platform's algorithm enhances message dissemination, reaching previously inaccessible demographics. This research highlights TikTok's evolution into a hub for credible healthcare information, fostering active viewer participation and creating a dynamic learning environment. It serves as a valuable resource for social media users seeking reliable healthcare information and provides content creators with a framework for developing impactful healthcare content. Furthermore, it underscores the potential for commercialization, wherein healthcare organizations, practitioners, and brands can collaborate with influencers to promote health products and services while advancing public health awareness on TikTok. The study reveals a high level of effectiveness in healthcare education on TikTok, with a mean effectiveness score of 3.29. Moreover, it indicates a considerable level of effectiveness among users, with a mean awareness score of 3.67.